2012
DOI: 10.4236/ojpm.2012.21014
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of mental health service use and risk of injury: A longitudinal study

Abstract: Objective: The aim of this study is to investigate the association between mental health treatment patterns and risk of injuries among a Western Australian male birth cohort. Method: A population-based birth-cohort of males born between 1980 and 1984 in Western Australia was followed up using linked health data. Results: Participants with mental health conditions were at an increased risk of injury. Those with a continuous mental health treatment pattern without interruption or window periods had lower risk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…These cross-sectional findings have been supported by some longitudinal research; for example, a study by Cameron et al [ 12 ] using health service data reported that individuals hospitalised for unintentional injury were more likely to experience mental health concerns in the ten years prior to the injury’s occurrence. A similar data linkage study in Australia found that males were more likely to experience an injury-related hospitalisation if they had previously been engaged with mental health services, particularly if their mental health care had been interrupted [ 13 ]. Longitudinal relationships between occupational injury and depression have also been examined [ 14 ], with gender differences detected in the patterns of association: males experiencing workplace injury were found to be more vulnerable to post-injury depression (compared with non-injured males), while female workers with depression were more likely to be injured at work (compared with non-depressed female workers).…”
Section: Introductionmentioning
confidence: 99%
“…These cross-sectional findings have been supported by some longitudinal research; for example, a study by Cameron et al [ 12 ] using health service data reported that individuals hospitalised for unintentional injury were more likely to experience mental health concerns in the ten years prior to the injury’s occurrence. A similar data linkage study in Australia found that males were more likely to experience an injury-related hospitalisation if they had previously been engaged with mental health services, particularly if their mental health care had been interrupted [ 13 ]. Longitudinal relationships between occupational injury and depression have also been examined [ 14 ], with gender differences detected in the patterns of association: males experiencing workplace injury were found to be more vulnerable to post-injury depression (compared with non-injured males), while female workers with depression were more likely to be injured at work (compared with non-depressed female workers).…”
Section: Introductionmentioning
confidence: 99%